THE ANALYSIS OF HEALTH PROMOTION STRATEGIES ON COMMUNITY PARTICIPATION IN PREVENTING STUNTING FOR MOTHERS WITH TODDLERS AT BANGUN PURBA SUB-DISTRICT - Siregar, Maria Putri Rezeki; Rochadi, R. Kintoko; Andayani, Lita Sri (jfpublisher, 2023)
Introduction. Stunting is a growth disorder in children under five due to chronic malnutrition and recurrent infections. Therefore, efforts are needed to increase community participation in preventing stunting and the strategy to implement a health promotion strategy. Bangun Purba sub-district has been included in the stunting locus since 2020. This study aimed to analyze health promotion strategies (advocacy, partnerships, and community empowerment) on community participation in stunting prevention. Method. This type of research was a mixed method with an explanatory sequential design with a quantitative approach of interviewing 131 respondents and qualitative with in-depth interviews with 10 informants. The data were analyzed using univariate, bivariate and multivariate analysis (logistic regression). Result & Analysis. The results showed that 49.6% of respondents stated that advocacy was not good, there was an influence between advocacy and community participation (p=0.046), but the implementation of advocacy was good enough, along with public commitment and government support. The partnership was stated by 72.2% of respondents in the not good category because partnerships in stunting prevention not implemented optimally, there was an influence between partnerships on community participation (p=0.042). Community empowerment was stated by 72.5% of respondents in not good category due to activities not running actively, there was an influence between community empowerment on community participation (p=0.038). The community empowerment variable was the greatest variable influence on community participation with OR = 0.536. Discussion. Good coordination and synergize well in the prevention and control of stunting so that Deli Serdang Regency becomes a stunting-free Regency.